Superior Mesenteric Artery Syndrome due to a Vertebral Hemangioma and Postpartum Osteoporosis following Treatment - Mehmet Elmadag; Yunus Güzel; Gokcer Uzer; İbrahim Tuncay (Case Reports in Orthopedics)
In pregnancy, advanced vertebral hemangiomas may be seen, and these require treatment. The case reported here is of a 35-year-old female in the 32nd week of pregnancy who was admitted to the orthopaedics clinic with a history of backache and difficulty walking. A burst fracture of L1 associated with a vertebral hemangioma was identified with an L3 compression fracture secondary to osteoporosis. The local kyphosis angle between T12 and L2 was 27°. Kyphotic deformity was corrected and postoperatively, the measured T12–L2 local kyphotic angle was 9°. Twelve hours postoperatively, oral nutrition was allowed, but she developed nausea and vomiting and twenty-four hours postoperatively, an electrolyte imbalance developed. Postoperatively, the patient was diagnosed with superior mesenteric artery syndrome. To the best of our knowledge, this is the first reported case of superior mesenteric artery syndrome, which occurred following the correction of a kyphotic deformity that had developed secondary to an advanced hemangioma in pregnancy.